The impact of community medical camps on medical students and graduates’ education - Fasih Ali Ahmed; Russell Seth Martins; Danish Ali; Mian Arsam Haroon; Amber Mehmood; Nuzhat Faruqui (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate the impact of volunteering at community medical camps on medical students’ and graduates’ clinical and soft skills, knowledge of community health, and future career goals. Method: The cross-sectional pilot study was conducted at the Aga Khan University Hospital, Karachi from July to October 2020, and comprised medical students or trainees who had attended at least one medical camp in a community-based setting organised by any of the two non-governmental organisations who collaborated in the study. Responses were obtained through a self-reported online survey from the participants. Data was analyzed using SPSS 25. Results: Of the 52 subjects, there were 25(48.9%) males and 27(51.9%) females with overall mean age 25.4±3.8 years. Majority of the participants 35(67.3%) had attended a private first-tier medical school while 17(32.7%) had attended other local medical schools. Overall, 40(76.9%) subjects reported improved community knowledge, , 44(84.6%) had experiential learning and confidence in outpatient management, and 49(94%) had improved soft skills. Besides, 21(40.4%) participants agreed to have been influenced to pursue a career in primary care, and 25(48.1%) reported a direct impact on their choice of career specialty. Compared to males, females reported improved more awareness and alertness (p=0.016), increased confidence approaching communities (p=0.032), and increased compassion towards patient care (p=0.047). Conclusions: Community-based medical camps had an overall positive impact on volunteering medical students. Key Words: Community medical camps, Community health service, Medical education, Service-learning.